Rancang Bangun Pengendali Hoist Crane Berbasis Jaringan Menggunakan Aplikasi Android - Rivo Restu Ananda Putra; Sri Mulyanto Herlambang; Henna Nurdiansari (Fakultas Teknik Universitas Maritim AMNI Semarang, 2025)
The phenomenon that occurs in the load lifting system is the need for an efficient and reliable mechanism to move the crane hoist pulley vertically and horizontally. This study aims to design and test a crane hoist system that uses a DC motor and a stepper motor controlled by an L293D motor driver, and to develop an application based on MIT App Inventor to control the movement of the motor. The research method used is integrated hardware and software design, followed by testing the performance of the motor, driver, and the application developed. Testing was carried out under limited load conditions, to measure the motor speed, voltage, and current used at loads of 10 to 100 grams. The results of the study showed that the system can function well at varying speeds, and the motor is able to lift a maximum load of up to 100 grams with a speed that decreases according to the weight of the load. The MIT App Inventor application successfully controls the motor effectively via a WiFi connection with a maximum distance of 10 meters, and loads the operation of the crane vertically and horizontally. This study proves that the designed system is able to work optimally in lifting and moving loads, and the application developed provides easy and efficient control.